City and territory in Majorca: A review of Majorcan “macrocephaly” - Mestre Morey, Margalida (Documents d’Anàlisi Geogràfica, 2015)
As a consequence of the tourism revolution which began in the 1960s, the relationship between the city of Palma and the rest of the urban system of Majorca has been increasingly described by the term “macrocephaly”. However, after analysing the evolution of the Majorcan population in recent decades, we have found that the hypothesis of an excessive concentration of population in Palma is increasingly difficult to sustain. To analyse this topic, some classical methodologies on the hierarchy of urban systems have been used, such as the rank-size model, the primacy index, and some indicators to measure population dispersion. The article concludes that this urban system can no longer be analysed by opposing the urban centre of Palma to the rest of the island territory, but instead by recognising that Majorca is already an integrated and interdependent system.